2021
DOI: 10.1186/s13148-021-01035-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic age acceleration is associated with cardiometabolic risk factors and clinical cardiovascular disease risk scores in African Americans

Abstract: Background Cardiovascular disease (CVD) is the leading cause of mortality among US adults. African Americans have higher burden of CVD morbidity and mortality compared to any other racial group. Identifying biomarkers for clinical risk prediction of CVD offers an opportunity for precision prevention and earlier intervention. Results Using linear mixed models, we investigated the cross-sectional association between four measures of epigenetic age ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 55 publications
4
54
1
Order By: Relevance
“…Both an American and a Scottish study among 969 and 5100 adults, respectively, reported that positive age acceleration as estimated by the clock of Hannum, but not that of Horvath, was associated with hypertension [ 26 , 28 ]. A study among 1100 mostly hypertensive African-Americans reported that positive age acceleration was associated with blood pressure, using Horvath’s and Hannum’s clocks [ 27 ]. In addition, this study, as well as two studies among 4178 women from the Women’s Health Initiative, only reported associations with systolic but not diastolic blood pressure when using the PhenoAge and GrimAge clocks [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both an American and a Scottish study among 969 and 5100 adults, respectively, reported that positive age acceleration as estimated by the clock of Hannum, but not that of Horvath, was associated with hypertension [ 26 , 28 ]. A study among 1100 mostly hypertensive African-Americans reported that positive age acceleration was associated with blood pressure, using Horvath’s and Hannum’s clocks [ 27 ]. In addition, this study, as well as two studies among 4178 women from the Women’s Health Initiative, only reported associations with systolic but not diastolic blood pressure when using the PhenoAge and GrimAge clocks [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building on prior theorizing [41], we tested a model in which demethylation of the two CpG sites on FKBP5 previously shown to be demethylated in response to stress and ageing, set in motion a broader set of biological changes captured by indices of accelerated ageing and ultimately lead to elevated risk for cardiometabolic illness [47]. In keeping with Levine et al (2018) [26], and more recently Ammous et al (2021) [30], we proposed that currently available DNA methylation-based indices of intrinsic accelerated ageing would potentially capture the impact of FKBP5-2 demethylation on a range of biological systems, and so constitute an intermediate step in the progression to elevated cardiometabolic risk (i.e., elevated blood pressure, elevated HbA1c, blood sugar, inflammation, BMI). These considerations led to our expectation that there would be a significant association of FKBP5-2 with accelerated ageing (AA), significant indirect effects from FKBP5-2 to two measures of cardiometabolic risk (CMR and FCMR10), and that similar patterns of association would be observed across the lifespan for both outcomes, using intrinsic measures of AA.…”
Section: Discussionmentioning
confidence: 94%
“…If methylation of these two FKBP5 loci are a reflection of biological embedding of early risk [35][36][37][38]58,59], and continue to exert an influence across the lifespan, we would expect to observe associations between their methylation levels and DNA methylation-based indices of accelerated ageing, which in turn would lead to elevated CMR (e.g [30]. Ammous et al, 2021).…”
Section: Is Fkbp5 Methylation An Epigenetic Marker Of Childhood Early Exposure To Danger?mentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetics plays a major role in the occurrence and progression of several CVDs, such as cardiac hypertrophy, heart failure, ischemic heart disease, aortic aneurysm, vascular calcification, and pulmonary hypertension, by mediating gene expression and cellular function (13). Furthermore, epigenetics implies the heritable alteration in the gene expression landscape without alterations in DNA sequence caused by the changes in nucleosome remodeling, which represents the architecture of chromatin and regulates the accessibility of DNA (14). The altered nucleosome remodeling is attributed to the interaction between the environment and the genome (15).…”
Section: Introductionmentioning
confidence: 99%